Immunomodulatory Properties of Pancreatic Islet-Derived Stem Cells Co-Cultured with T cells: Does It Contribute to the Pathogenesis of Type 1 Diabetes? - Sariboyaci, A. E.; Demircan, P. C.; Gacar, G.; Unal, Z. S.; Erman, G.; Karaoz, E. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Previously, we isolated stem cells from rat pancreatic islets (rPI-SCs) with similar characteristics of bone-marrow derived-mesenchymal stem cells (MSCs). We aimed to investigate the immunomodulatory effects of them on stimulated T-cells.Following in vitro co-culturing directly and indirectly, the response of T-cells stimulated by concanavalin-A and immunosuppressive activity of rPI-SCs were evaluated by analysing in terms of cell viability, proliferation and apoptosis, cell cycle, differentiation of Treg, cytokines and some regulatory factors produced from T and SCs.Our results have firstly demonstrated that rPI-SCs like MSCs could regulate stimulated T-cell responses by altering their cell-cycle and cytokine profile, inhibiting the cell proliferation, and inducing the apoptosis and differentiation of Treg. Direct and indirect in vitro co-cultures of rPI-SCs with stimulated T-cells showed immunosuppressive effects.Therefore, we are introducing a novel type of stem cell with immunomodulatory properties. On the other hand, it is questionable why PI-SCs cannot protect the insulin producing cells from attacks of autoreactive T-cells in the developing of type1 diabetes. For this purpose, further molecular researches in vitro and in vivo are needed to clarify why PI-SCs may not suppress attacks of autoreactive-immune-cells towards PIs. PI-SCs from diseased people should be compared with pancreas of healthy ones at both genomic and proteomic levels.
Keywords: characterization; immunosuppression; pancreatic islets; stem cells